Construction Safety Using Visual Technological Support - Alfredo Soeiro (2021)
The 14th International Conference on Interactive Mobile Communication Technologies and Learning, IMCL2021, is part of an international initiative to promote technology-enhanced learning and online engineering world-wide. The IMCL2021 conference will cover all aspects of mobile learning as well as the emergence of mobile communication technologies, infrastructures and services and their implications for education, business, governments and society. The IMCL2021 aims to promote the development of mobile learning, to provide a forum for education and knowledge transfer, to expose students to latest ICT technologies and encourage the study and implementation of mobile applications in teaching and learning. The conference will also aim to stimulate critical debate on theories, approaches, principles and applications of mobile learning among educators, developers, researchers, practitioners and policy makers.